Hubungan Kondisi Lingkungan Rumah dan Kebiasaan Merokok Anggota Keluarga Dengan Kejadian ISPA Pada Balita Di Kampung Pepayungen Angkup Kecamatan Aceh Tengah - Maulina Iriyanti, (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
ARI is a respiratory tract infection that lasts for 14 days. Acute Respiratory Infection (ARI) is a disease that is commonly found in toddlers and children ranging from mild to severe ARI. Based on data obtained from the Central Aceh District Health Office in 2023, ARI was ranked second only to diarrhoea at the health centre level at 2166 cases. ARI can occur due to unhealthy home environment conditions. Poor home environment can affect health and respiratory tract disorders. In addition to environmental factors, host factors such as smoking habits are also one of the factors causing ARI in toddlers. This study aims to determine the relationship between home environmental conditions and smoking habits of family members with the incidence of ARI in toddlers in Pepayungen Angkup village. This research is analytical with cross sectional design. The sample in this study was 69 mothers who had toddlers using simple random sampling technique. This study was conducted in March 2023 for 7 days using a research instrument in the form of a questionnaire, data analysis using the chi-square test. The results showed that there was a significant relationship between home ventilation and the incidence of ARI in toddlers with a P value of 0.009. There is a significant relationship between parental smoking habits and the incidence of ARI in toddlers in Pepayungen Angkup village with a P value of 0.002. The conclusion is that there is a relationship between home ventilation and parental smoking habits with the incidence of ARI in toddlers in Pepayungen Angkup village, Central Aceh Regency.